Changing trends in indication of cesarean section in a tertiary care centre of Central India - Patil, Pooja; Bhardwaj, Malini; Sharma, Priyanka; Chandrakar, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was carried out to find the rate of Cesarean section (CS) in our institute from 2012 to 2016 and also to find any change in the indications of CS over these five years. Methods: A retrospective analysis of data was done from the records of the patients who underwent CS and the rate of Cesarean section and the indications were noticed. Results: The rate of Cesarean section has increased from 43.85% in 2012 to 48.18% in 2016. There is increase in the number of Primary Cesarean cases from 61.8% in 2012 to 68.4% in 2016.The percentage of Elective CS has increased in last five years from 10.2% in 2012 to 23.6% in 2016 which is due to the drastic increase in Elective Repeat CS from 13.3% in 2012 to 43.4% in 2016. The first and second major indication of Primary CS over the years remained the same i.e. fetal distress and CPD. Other major contributing indications were Non-progress of labour, failed induction and Malpresentation. Oligohydraminos and IUGR, Multiple pregnancy and precious pregnancy have emerged as the major indication in last three years. Previous CS and Previous 2 CS contributed as the main indication for Elective CS. Conclusions: The rate of Cesarean section need to be reduced. The overall main indication for CS was Previous CS and thus Primary CS rate should be reduced. Fetal distress being the main indication for Primary CS should be further confirmed by fetal scalp pH findings and Repeat CS cases should be given more trial of labour.